THERMAL COMFORT IN INDIVIDUAL SHELTERS FOR CALVES WITH NON-CONVENTIONAL CEILING MADE OF AGRO-INDUSTRIAL BY-PRODUCTS - de Castro Júnior, S. L.; de Oliveira, D. C. G.; Caneppele, F. L.; Fiorelli, J. (Revista Brasileira de Engenharia de Biossistemas, 2017)
This study evaluated the thermal comfort conditions in two individuals calve shelter models covered with fiber cement tile without ceiling and using a ceiling made of low density particleboards from agro-industrial by-products (40% sugarcane bagasse and 60% Pinus sp. shavings) bonded with polyurethane bi-component resin based on castor oil. In the ambience study, dry bulb temperature (DBT), black globe temperature (BGT) and relative humidity (RH) of the calf hutches were evaluated. Indices, such as Black Globe Temperature and Humidity Index (BGHI) and Radiant Thermal Load (RTL), and also thermographic images of the internal surface of the shelters were studied. The use of fuzzy modeling has been proposed, allowing the comparison of the BGT, BGHI and RTL indices, and via these values, attributing the comfort situation, thus seeking to optimize the experimental evaluations. The results indicate that the presence of the ceiling did not contribute to a heat level reduction inside the shelters, which presented above the comfort conditions for the animals during the summer. Through observation, there was a reduction of the internal temperature of the surfaces of the shelter with a ceiling.